Advancing macromolecular structure determination with microsecond X-ray pulses at a 4th generation synchrotron - Julien Orlans; Samuel L. Rose; Gavin Ferguson; Marcus Oscarsson; Alejandro Homs Puron; Antonia Beteva; Samuel Debionne; Pascal Theveneau; Nicolas Coquelle; Jerome Kieffer; Paolo Busca; Jeremy Sinoir; et al. (Communications Chemistry)
Abstract Serial macromolecular crystallography has become a powerful method to reveal room temperature structures of biological macromolecules and perform time-resolved studies. ID29, a flagship beamline of the ESRF 4th generation synchrotron, is the first synchrotron beamline in the world capable of delivering high brilliance microsecond X-ray pulses at high repetition rate for the structure determination of biological macromolecules at room temperature. The cardinal combination of microsecond exposure times, innovative beam characteristics and adaptable sample environment provides high quality complete data, even from an exceptionally small amount of crystalline material, enabling what we collectively term serial microsecond crystallography (SµX). After validating the use of different sample delivery methods with various model systems, we applied SµX to an integral membrane receptor, where only a few thousands diffraction images were sufficient to obtain a fully interpretable electron density map for the antagonist istradefylline-bound A2A receptor conformation, providing access to the antagonist binding mode. SµX, as demonstrated at ID29, will quickly find its broad applicability at upcoming 4th generation synchrotron sources worldwide and opens a new frontier in time-resolved SµX.